Dracula - "Stoker , Bram" (Longman Group Ltd: China, 1995)
Jonathan Harker's visit to mysterious Count Dracula's eerie castle in Transylvania is just the start of a insidious plan to send vampires to England
Keywords: Vampires Fiction readers